2010
DOI: 10.1051/limn/2010024
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and abundance of aerobic anoxygenic phototrophic bacteria in two cyanobacterial bloom-forming lakes in China

Abstract: -Aerobic anoxygenic phototrophic (AAP) bacteria are widely distributed in marine and freshwater ecosystems. The aims of this study were to investigate the diversity and abundance of AAP bacteria in cyanobacterial bloom-forming eutrophic lakes and to study the association of AAP bacteria with the bloomforming cyanobacteria. Analysis of pufM gene (the light-reaction center gene) clone libraries indicated that in eutrophic lakes (Lake Taihu and Lake Chaohu, China) with cyanobacterium Microcystis blooms, the AAP b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 24 publications
1
5
1
Order By: Relevance
“…The high abundance of puf M gene from eutrophic DC and CH was consistent with the previous study by Shi et al [14] on eutrophic lakes Taihu and Chaohu in China. Result showed that free-living AAP bacteria were separately 2.3 (±0.69) × 10 6 cells mL -1 in Lake Taihu and 1.3 (±0.29) × 10 5 cells mL -1 in Lake Chaohu, which was higher than the previously reported levels in other eutrophic freshwater bodies [14].…”
Section: Abundances Of Pufm Genesupporting
confidence: 92%
See 2 more Smart Citations
“…The high abundance of puf M gene from eutrophic DC and CH was consistent with the previous study by Shi et al [14] on eutrophic lakes Taihu and Chaohu in China. Result showed that free-living AAP bacteria were separately 2.3 (±0.69) × 10 6 cells mL -1 in Lake Taihu and 1.3 (±0.29) × 10 5 cells mL -1 in Lake Chaohu, which was higher than the previously reported levels in other eutrophic freshwater bodies [14].…”
Section: Abundances Of Pufm Genesupporting
confidence: 92%
“…Result showed that free-living AAP bacteria were separately 2.3 (±0.69) × 10 6 cells mL -1 in Lake Taihu and 1.3 (±0.29) × 10 5 cells mL -1 in Lake Chaohu, which was higher than the previously reported levels in other eutrophic freshwater bodies [14]. The abundance of AAP bacteria was highly variable with copies of puf M gene ranging from 1.1 × 10 2 to 1.4 × 10 5 mL -1 [21] and 0.3 to 12.04 × 10 5 cells mL −1 in the surface layers of peat-bog lakes by epifluorescence microscopy numbering [13].…”
Section: Abundances Of Pufm Genecontrasting
confidence: 63%
See 1 more Smart Citation
“…AAP bacteria are abundant in various marine environments (Kolber et al, , Cottrell et al, , Sieracki et al, , Jiao et al, , Yutin et al, , Boeuf et al, ) and also in many freshwater lakes and rivers (Mašín et al, , Mašín et al, , Ruiz‐González et al, , Čuperová et al, , Caliz and Casamayor, , Fauteux et al, , Lew et al, ). Freshwater AAP bacteria seem to represent a diverse assemblage of species belonging exclusively to different subgroups of Alpha‐ and Betaproteobacteria (Waidner and Kirchman, , Shi et al, , Salka et al, , Čuperová et al, , Caliz and Casamayor, ).…”
Section: Introductionmentioning
confidence: 99%
“…Different reports on eutrophic lakes of China (Taihu, Chaohu and Ulungur Lakes) revealed the invariable predominance of Microcystis sp. (Ye et al 2009 ;Shi et al 2010 ;Lin et al 2011 ). Magana-Arachchi et al ( 2011 ) studied the cyanobacterial diversity of Gregory Lake, Nuwara Eliya, Sri Lanka which is eutrophied due to agricultural and industrial activities.…”
Section: Cyanobacterial Diversity In Aquatic Bodiesmentioning
confidence: 99%